2015
DOI: 10.1213/ane.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch and Acute Kidney Injury in Orthotopic Liver Transplantation

Abstract: Background Acute kidney Injury (AKI) is a frequent complication of orthotopic liver transplantation (OLT). Hepatic failure pathophysiology and intraoperative events contribute to AKI after OLT. Colloids are routinely used to maintain intravascular volume during OLT. Recent evidence has implicated 6% hydroxyethyl starch (HES) (130/0.4) with AKI in critically ill patients. Methods We performed a retrospective cross-sectional analysis of electronic anesthesia records, surgical dictations, and perioperative lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…[114][115][116][117] ii8 | Goren and Matot AKI. 91 108 112 117 118 In a recent paper, Hartog and colleagues 119 raised concerns regarding the intraoperative use of HES and concluded that in the absence of proven benefit and considering the methodological problems with studies supporting the use of HES, they do not recommend use of HES solutions in any clinical situation.…”
Section: Choice Of Fluid Solutionmentioning
confidence: 99%
“…[114][115][116][117] ii8 | Goren and Matot AKI. 91 108 112 117 118 In a recent paper, Hartog and colleagues 119 raised concerns regarding the intraoperative use of HES and concluded that in the absence of proven benefit and considering the methodological problems with studies supporting the use of HES, they do not recommend use of HES solutions in any clinical situation.…”
Section: Choice Of Fluid Solutionmentioning
confidence: 99%
“…To further complicate the results, several surgical studies including cardiac surgery have been retracted after scientific misconduct 20 . Recently, there were a few new observational studies on hydroxyethyl starch and AKI in non-cardiac surgeries 7,8 . Our goal was to look specifically at cardiac surgical population due to the unique physiological changes that CPB predisposes and compare two different types of 6% HES and their effects on the development of postoperative AKI and the need for blood product transfusion in comparison to patients who did not receive HES.…”
Section: Introductionmentioning
confidence: 99%
“…62 Given the uncertainty regarding the safety of artificial colloids (gelatin and hydroxyethyl starch) in liver transplantation patients, we routinely use albumin 4% bolus of 3 mL/Kg as a fluid challenge, as well as blood products. 63 Last but not least, liver transplantation is associated with increased bleeding, mostly as a result of bad fluid therapy. 64 However, it should be recalled that although LT is associated with increased bleeding, altered coagulation with a prothrombotic state may also occur.…”
Section: Fluid Replacementmentioning
confidence: 99%